A study on one‐dimensional consolidation of layered structured soils. (8th November 2015) - Xie, Kang‐He; Xia, Chang‐Qing; An, Ran; Ying, Hong‐Wei; Wu, Hao
Summary: The governing equations for one‐dimensional consolidation of layered structured soils under time‐dependent loading are established. Using simplified k‐σ ′ and mv ‐ σ ′ models, n ‐layered structured soils are transformed into ( n  + 1) or ( n  + 2)‐layered soils in which the thickness of upper and lower layers are gradually changing. The approximate solutions for the governing equations are then obtained under two types of boundary conditions, and the computer program is developed. Based on the solutions and computer program, the consolidation behavior of layered structured soils with soft interlayer is studied. It is shown that the permeability and compressibility of the soft interlayer have the greatest influences on the rate of settlement and rate of the dissipation of excess pore water pressure. Copyright © 2015 John Wiley & Sons, Ltd.